Bullying dan Catcalling di Kalangan Pelajar: Tantangan Kekerasan Sosial Dalam Dunia Pendidikan - Rika Aulia Maharani Srg; Raisya Rhadella Br Ginting; Nurhayati (Pusat Riset dan Inovasi Nasional, 2025)
This research focuses on analyzing the different types of social violence that arise in schools, with a particular focus on bullying and catcalling among students. This research was carried out through two community service programs organized by Public Health Science students from the State Islamic University of North Sumatra (UINSU) at SMPN 34 Medan and SMAN 5 Binjai. The method used is a descriptive quantitative approach with data collection through questionnaires and interviews. The results of the study show that bullying is still an important problem at the junior high school level, especially in verbal form, while catcalling occurs a lot in high school and is influenced by social aspects such as peers and social media. The effects of these two behaviors are detrimental to students' mental health, including causing stress, anxiety, and decreased academic achievement. Although some schools have implemented prevention programs, more efforts are still needed to improve the effectiveness of their implementation. This study recommends the need for continuous education, active involvement of teachers, and cooperation between schools and parents to create a safe learning environment and support the mental development of students.